The effects of conceptual style preference, related cognitive variables and sex on achievement in mathematics - Roach, Donald Ashworth (1979)
The Conceptual Style Test, a mathematics achievement test and an intelligence test were administered to Grade 6 children (206 boys and 212 girls) in five urban primary schools. The results showed that: 1) mathematics achievement had significant positive correlations to analytic conceptual style and intelligence; 2) girls had higher mathematics achievement than boys; and 3) analytic conceptual style had a significant positive correlation with intelligence, but had no relation to gender. When intelligence was partialled out, the relation between conceptual style preference and mathematics achievement became non-significant
DOI: 10.1111/j.2044-8279.1979.tb02399.x
Keywords: Gender analysis